2012
DOI: 10.1002/ajpa.22058
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin, fatherhood, and reproductive behavior in human males

Abstract: Although humans are considered unusual among mammals for the intensity of care that fathers often provide offspring, little is known about the hormonal architecture regulating human paternal investment. Prolactin has important reproductive functions in both female and male mammals and other taxa, making it a candidate regulator of human paternal behavior. Notably, prolactin is higher during periods of offspring care in some species, but it is unknown if this pattern occurs in human fathers. We draw on a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 81 publications
(117 reference statements)
2
47
1
1
Order By: Relevance
“…PRL reduces hypothalamic-pituitary-adrenal (HPA) activity and was found to have antistress effects in rats (Donner, Bredewold, Maloumby, & Neumann, 2007;Schlein, Zarrow, & Denenberg, 1974;Torner, Toschi, Pohlinger, Landgraf, & Neumann, 2001). In addition, PRL appears to be involved in human fatherhood (Gettler, McDade, Feranil, & Kuzawa, 2012;Gordon et al, 2010b), and lower levels of PRL were found in fathers compared to nonfathers, which further decline after father-infant interaction (Gettler et al, 2011). Yet, while two studies showed correlations between PRL and depression following spouse loss (Jacobs et al, 1986;Lane et al, 1987), no study examined PRL in romantic attachment in humans.…”
mentioning
confidence: 96%
“…PRL reduces hypothalamic-pituitary-adrenal (HPA) activity and was found to have antistress effects in rats (Donner, Bredewold, Maloumby, & Neumann, 2007;Schlein, Zarrow, & Denenberg, 1974;Torner, Toschi, Pohlinger, Landgraf, & Neumann, 2001). In addition, PRL appears to be involved in human fatherhood (Gettler, McDade, Feranil, & Kuzawa, 2012;Gordon et al, 2010b), and lower levels of PRL were found in fathers compared to nonfathers, which further decline after father-infant interaction (Gettler et al, 2011). Yet, while two studies showed correlations between PRL and depression following spouse loss (Jacobs et al, 1986;Lane et al, 1987), no study examined PRL in romantic attachment in humans.…”
mentioning
confidence: 96%
“…Fathers with higher prolactin concentrations were more responsive to infant cries (Fleming et al, 2002) and they spent more time engaged in coordinated play with their infants than other men (Gordon et al, 2010b). Prolactin concentrations are higher in fathers than non-fathers in a sample of highly paternal men in the Philippines (Gettler et al, 2012a), whereas Grey (2007) found no difference in prolactin concentrations between residential and non-residential Jamaican fathers.…”
Section: Prolactinmentioning
confidence: 90%
“…763,764 Whilst numerous studies in a range of species, including humans, 765,766 have found an association between prolactin and paternal care, 767 the role that prolactin plays in the induction of paternal behavior is unclear and controversial, even in rodents. 763,764 Whilst numerous studies in a range of species, including humans, 765,766 have found an association between prolactin and paternal care, 767 the role that prolactin plays in the induction of paternal behavior is unclear and controversial, even in rodents.…”
Section: Paternal Behaviormentioning
confidence: 99%